PENGARUH CITRA MEREK (BRAND IMAGE) TERHADAP LOYALITAS KONSUMEN ROKOK GUDANG GARAM PADA KONSUMEN ROKOK DI WILAYAH PENFUI - Crecencio M S D Quintas; Tri Suris Lestari (Universitas Boyolali, 2018)
This research is intended to collect all relevant data and information relating toconsumer loyalty to salt cigarette brand in Penfui area. This study aims to determine theinfluence of brand image (brand image) on consumer loyalty Tobacco cigarettes tocigarette consumers in the penfui area. Consumer loyalty is an important thing for acompany to do to overcome the tight competition in the business world today. One way togain competitive advantage in maintaining consumer loyalty is to establish a good brandimage in the eyes of consumersThe population in this research is cigarette consumer consuming salt cigarettewarehouse in Penfui area as many as 100 people, the sample in this research usingaccidental technique, where the sample is taken as 100 people. The data obtainedobtained in this study are qualitative and quantitative data, primary data and secondarydata, data collection techniques using questionnaires and observations. After the data arecollected in the validity test, reliability and simple linear regression analysis techniques.From the result of validity test shows that the value is significantly below thenumber 0.05, so it can be said all the variables and indicator items question riabel BrandImage and Consumer Loyalty is valid. Reliability test results showed that all the variableshave a large enough Alpha coefficient, which is above 0.6 so it can be concluded that allitems measuring the variable of the questionnaire is reliable which means that thequestionnaire used in this study is a reliable questionnaire. From the results of simpleLinear regression test says Y = 4.401 + 0.297 X, Deterinasi coefficient test results (R2)obtained R Square magnitude is 0,552 it states 55,2% Consumer loyalty can be explainedby variable quality of brand image.While the remaining 44.8% is another variable notincluded in this study.Companies must be able to maintain or even enhance the image formed forconsumers of GudangGaram Cigarette Consumers, for example by giving awareness tothe public (consumers) to love their own country's products through some marketingprograms or to find out customer expectations of PT GudangGaram products, Companiescan produce better product variants and meet those expectations. It is important torealize that keeping customers far better and more profitable than looking for newcustomers to become customers, therefore companies need to pay more attention toservice to their customers.